IL-15 trans-presentation by pulmonary dendritic cells promotes effector CD8 T cell survival during influenza virus infection - McGill, Jodi (The Rockefeller University Press, 2010)
We have recently demonstrated that peripheral CD8 T cells require two separate activation hits to accumulate to high numbers in the lungs after influenza virus infection: a primary interaction with mature, antigen-bearing dendritic cells (DCs) in the lymph node, and a second, previously unrecognized interaction with MHC I–viral antigen–bearing pulmonary DCs in the lungs. We demonstrate that in the absence of lung-resident DC subsets, virus-specific CD8 T cells undergo significantly increased levels of apoptosis in the lungs; however, reconstitution with pulmonary plasmacytoid DCs and CD8α(+) DCs promotes increased T cell survival and accumulation in the lungs. Further, our results show that the absence of DCs after influenza virus infection results in significantly reduced levels of IL-15 in the lungs and that pulmonary DC–mediated rescue of virus-specific CD8 T cell responses in the lungs requires trans-presentation of IL-15 via DC-expressed IL-15Rα. This study demonstrates a key, novel requirement for DC trans-presented IL-15 in promoting effector CD8 T cell survival in the respiratory tract after virus infection, and suggests that this trans-presentation could be an important target for the development of unique antiviral therapies and more effective vaccine strategies.